Intermolecular proteolytic processing of SPRING and Site-1-protease regulate SREBP signaling - Hendrix, Sebastian; Tan, Josephine M.E.; Ndoj, Klevis; Valiloo, Masoud; Zijlstra, Lobke F.; Ottenhoff, Roelof; Seidah, Nabil G.; Loregger, Anke; Zelcer, Noam (bioRxiv, 2023)
The SREBP transcription factors are central regulators of fatty acid and cholesterol metabolism. Produced as membrane-resident precursor proteins in the ER, their transcriptional activation requires the cholesterol-dependent translocation to the Golgi, and subsequent proteolytic cleavage by S1P, a type-I transmembrane protein. S1P is produced as a proprotein convertase that needs to undergo autocatalytic cleavage to attain its mature form in the Golgi, in a process that is not fully elucidated. We have recently identified SPRING (C12ORF49) as a novel regulator of the SREBP pathway and reported that S1P activity and retrograde recycling of the SREBP chaperone SCAP are affected. Here, we demonstrate that SPRING and S1P interact and that in co-transfection experiments in mammalian cells this facilitates the autocatalytic activation of S1PA→C form. Accordingly, S1PA→C processing of stably overexpressed S1P in SPRINGKO cells is attenuated, but not abolished, and does not rescue SREBP signaling. Reciprocally, we identified a conserved S1P cleavage site in SPRING, and demonstrate that cleavage of SPRING results in secretion of the SPRING ectodomain. SPRING cleavage is S1P-specific and can be pharmacologically inhibited by S1P inhibitors or by mutating the S1P cleavage site. Functional analysis revealed that the SPRING ectodomain was sufficient to support S1PA→C processing and SREBP signaling, but that SPRING cleavage is not a prerequisite for this. In conclusion, our study reveals a complex interplay between the proteolytic activation of S1P and SPRING yet suggests that this is not the primary mechanism underlying the role of SPRING in SREBP signaling.